40 Agile Methods in 40 Minutes - Smith, Craig (2014)
My presentation from Scrum Australia 2014 called “40 Agile Methods in 40 Minutes” is available on Slideshare. With 73% of the world using Sc rum as their predominant Agile method, this session will …